2015
DOI: 10.1097/mco.0000000000000121
|View full text |Cite
|
Sign up to set email alerts
|

Proline metabolism and cancer

Abstract: Purpose of reviewProline metabolism impacts a number of regulatory targets in both animals and plants and is especially important in cancer. Glutamine, a related amino acid, is considered second in importance only to glucose as a substrate for tumors. But proline and glutamine are interconvertible and linked in their metabolism. In animals, proline and glutamine have specific regulatory functions and their respective physiologic sources. A comparison of the metabolism of proline and glutamine would help us und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
125
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(136 citation statements)
references
References 38 publications
(57 reference statements)
5
125
0
1
Order By: Relevance
“…Fibrillary collagen synthesis, which is an important process in the proliferative phase of wound healing, requires the formation of proline and hydroxyproline [58]. Several other studies have shown that oxygen accelerates collagen synthesis and improves proline hydroxylase enzyme activity [59].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrillary collagen synthesis, which is an important process in the proliferative phase of wound healing, requires the formation of proline and hydroxyproline [58]. Several other studies have shown that oxygen accelerates collagen synthesis and improves proline hydroxylase enzyme activity [59].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Liu et al (34) showed that transcription factor MYC inhibits POX/PRODH expression and, thus, inhibits its function. microRNA miR-23b* an inhibitor of POX is highly expressed in different types of tumors (35,36). Due to the lack of POX, the conversion of proline to pyrroline-5-carboxylate (P5C) is altered (37), and subsequently the amount of proline in urine is increased.…”
Section: Resultsmentioning
confidence: 99%
“…3C). Interestingly, the glutamate derivatives proline, aspartate and glutathione are associated with proliferation and tumorigenesis (3438). …”
mentioning
confidence: 99%